Method And Implementation of MPLS Tunnel Selection On Nokia Metro-E Devices - R. Muhammad Arifin (Politeknik Negeri Semarang, 2021)
Tunneling is an interconnection solution between local networks separated by remote over a public IP. The current issue does not have proper guidelines for using tunneling techniques. Tunneling selection is generally only based on the beliefs and experience of network management operators or following SOP. The brand of tunneling device is widely used by telecommunication operators in Indonesia (especially P. Java) is Nokia. In this study, implementation, testing and analysis of MPLS techniques on Nokia devices to produce recommendations when to use MPLS tunnels according to network topology appropriately. The software used in this study was FTP, Tfgen and Wireshark. FTP and Tfgen as network traffic generators and Wireshark to record throughput, delay and downtime. Analysis of MPLS on Nokia devices is conducted based on recording results for various traffic engineering scenarios including loadless conditions, and various other conditions in case of network disruption. Mpls research results when without load all went well with an average throughput of 1.08 Mbps and delay of 10 ms. When with load has a stability delay of 10 ms, when when network disruption using ICMP get 1 Request Time Out or 4s. MPLS techniques are used on established networks because it can provide alternative density lines.